Effect of Foreign Equity Gross Purchases on Stock Market Volatility in Kenya : Empirical Evidence from Nairobi Securities Exchange - Isaac Linus Ochieng; Tobias O. Olweny; Oluoch J. Oluoch; Gordon O. Ochere (European Scientific Journal, ESJ, 2019)
The main objective of the study was to determine the effect of foreign equity purchases turn-over on the level of volatility at the Nairobi Securities Exchange. The study was twofold as it focused on the effect of foreign equity gross purchases on stock market volatility before and after introducing foreign exchange rate as a moderating variable. The span of the study was eight years from 2008 to 2015 as the period was marked by unprecedented world events such as the global economic recession and the post poll pandemonium in Kenya which subsequently affected foreign equity flows and the volatility in the equity bourse. The research design employed in the study was the causal research design. The target population of the study were the monthly foreign equity gross purchases, monthly Nairobi Securities Exchange 20 share indices and monthly USD Bid-Ask foreign exchange. The study samples in the study were the monthly foreign equity gross purchases, monthly Nairobi Securities Exchange 20 share indices and monthly USD Bid-Ask foreign exchange from May 2008 to December, 2015. Time series secondary data was used in the study. The data was subjected to diagnostic tests such as linearity test, multicollinearity test, normality test, test for homoscedasticity and test for autocorrelation with E-views being the main statistical tool of analysis. The main model used in the study was the vector error correction model subsequent to undertaking stationarity test, lag selection test and cointegration tests. Study results reveal a positive but in-significant effect of foreign equity purchases turn-over on stock market volatility and a negative but in-significant effect after introducing foreign exchange rate as a moderating variable. The study recommends adoption of efficacious cross-border listing rules to spur stock market integration that would subsequently increase foreign investor participation and development of apt financial derivative markets to aid in the mitigation of time-varying foreign currency risks as a consequence of foreign exchange risk exposure.